Additive manufacturing of alumina refractories by binder jetting - Enrico Storti; Patricia Kaiser; Marc Neumann; Alban Metallari; Filippo Gobbin; Hamada Elsayed; Jana Hubálková; Paolo Colombo; Christos G. Aneziris (Open Ceramics)
In this work, refractory components based on alumina were produced by binder jetting using a large-scale 3D printer. The formulation contained several particle fractions up to a grain size of 3 mm, equal to the printer resolution. The binder system contained fine dead burnt magnesia, milled citric acid and reactive alumina, which were added to the aggregate mixture to create the powder bed. Deionized water was deposited from the printer's nozzles and triggered the binding reaction between the magnesia and citric acid. After 24 h, the printed samples were removed from the powder bed, dried and sintered at 1600 °C for 5 h. Reactive alumina contributed to the in situ creation of magnesium aluminate spinel at high temperature. The samples were characterized in terms of Young's modulus of elasticity, bending and compressive strength in 2 directions (parallel and perpendicular to the printing direction). The broken parts were used to investigate physical properties such as the open porosity and bulk density. The microstructure was studied by means of computed tomography. Finally, powder samples were used to determine the phase composition at different stages of production by means of XRD.